Strengthening reading and writing in elementary education through didac-tic strategies based on colombian stories and tal - Ruano Ortiz, Huber Iván (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This article stems from the scientific problem identified by the question: How to strengthen the reading and writing processes in fourth and fifth-grade students of Primary Basic Education at the El Boquerón Educational Institution, Cauca, Colombia? The research showed a lack of interest in reading, insufficiencies in locating main ideas, an inability to construct meaning, inconsistencies in textual construction, and teachers who do not sufficiently motivate reading and writing, all of which negatively impact the ability to comprehend and construct text. There is also a lack of family support, affecting academic performance and cognitive development. The research revealed an opportunity for improvement, based on the preference of students (72%) and teachers (67%) for Colombian stories and tales. The intervention proposal titled "I tell a story and the more I tell, the more I understand" in the form of a strategy seeks to use culturally relevant narrative as a bridge to transform literacy into a meaningful and motivating process. It is based on a constructivist approach that encourages interaction, dialogue, and aesthetic enjoyment, positioning local and national narrative as an ideal tool to reconnect students with written language and enhance their cognitive and cultural development.